Music and History : Bridging the Disciplines - Pelkey, Stanley C.; Jackson, Jeffrey H., 1971- (Book collections on Project MUSE., 2005)
This book begins with a simple question: Why haven't historians and musicologists been talking to one another? Historians frequently look to all aspects of human activity, including music, in order to better understand the past. Musicologists inquire into the social, cultural, and historical contexts of musical works and musical practices to develop theories about the meanings of compositions and the significance of musical creation. Both disciplines examine how people represent their experiences. This collection of original essays, the first of its kind, argues that the conversation between s.